REVIEWING THE APPROACHES OF INDONESIA ON TRADEMARK DILUTION DOCTRINE - Rina Shahriyani Shahrullah (Magister Ilmu Hukum Fakultas Hukum Universitas Syiah Kuala, 2023)
Rights to well-known trademarks need legal protection. The well-known trademark case relates to the trademark dilution doctrine. This research aims to analyze and determine the legal doctrine of trademark dilution in Indonesia. The research used a normative juridical approach so that secondary data was collected by using library research methods. The conclusion of the research is that the regulation of the trademark dilution doctrine in Indonesian national law is still implied. However, provisions related to the trademark dilution doctrine in the Paris Convention for the Protection of Industrial Property Rights and the Agreement on Trade-Related Aspects of Intellectual Property Rights can be applied. The ssolution of violations of the trademark dilution doctrine in Indonesia under the Trademark Law is not optimal. The well-known trademark cases studied in this research meet the trademark dilution doctrine which contains the concept of passing off. The regulation on the trademark dilution of well-known trademark in Indonesia is still not perfect, so it is necessary to improve its legal substances.